Interaction of transport and land use: framework for an integrated urban model - Hubertus Phillippus Blijie; Michiel Adriaan de Bok (European Regional Science Association (ERSA), 2002)
The growing general concern on limited resources (e.g. space) have led to the conviction that policy makers, that deal with urban development, need to consider their choices carefully, with respect to the effects on urban development on the long term. Models that describe the urban development provide quantitative insight in the effects of possible government policy and are a useful tool for policy makers. In the last decade new generation computers have drastically increased data handling capacity and graphically possibilities, allowing much more detail in spatial modeling. This has resulted in research efforts into urban models to quantify the effects of spatial policy. The research, which will be described in this paper, aims for an integrated approach to spatial modeling with special attention on the influence of transport networks and the role of the government. Main objective of the research is the development and application of an urban model to quantify the effects of planning policies on the spatial development. At micro level this urban model simulates the reaction of actors to changes in the urban system: the development or renewal of new urban areas and new infrastructure. These changes are imposed on the urban system by government and developers on macro and meso level. The paper will present the theoretical framework for the proposed urban model and the objectives of the research. This will be complemented with a description of spatial planning issues in the Netherlands. In the proposed urban model the spatial system (urban region) is represented by multiple linked sub-systems. Individual sub-systems are: the housing market, public facilities, the market for business real estate and the transport system. Each sub-system is represented as a market with a supply and demand side. The government and (project) developers define the supply side through spatial policy and investments. On the demand side, agents (households and companies) react at changes in these subsystems. These reactions expose themselves as individual decisions whether to move to other dwellings or to relocate businesses. Development and application of modeling techniques for the choice behavior of households and companies as entities, are main objectives in the research. The urban markets have a strong coherence for the spatial relations of each agent. Quantification of these relationships, by analyzing the transportation facilities, is important in analyzing the choice behavior of households and companies. This is why the transport system plays a central role in the urban model. For each subsystem an appropriate modeling technique has been selected, based on an exploration of available approaches in the literature and other research programs. Efforts are under way to collect and operationalize the extensive data necessary for the modeling task.
Keywords: 330